2018
DOI: 10.1051/0004-6361/201832669
|View full text |Cite
|
Sign up to set email alerts
|

Pushing back the limits: detailed properties of dwarf galaxies in a ΛCDM universe

Abstract: We present the results of a set of high resolution chemo-dynamical simulations of dwarf galaxies in a ΛCDM cosmology. Out of an original (3.4 Mpc/h) 3 cosmological box, a sample of 27 systems are re-simulated from z=70 to z=0 using a zoom-in technique. Gas and stellar properties are confronted to the observations in the greatest details: in addition to the galaxy global properties, we investigated the model galaxy velocity dispersion profiles, half-light radii, star formation histories, stellar metallicity dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
172
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(181 citation statements)
references
References 175 publications
(266 reference statements)
9
172
0
Order By: Relevance
“…Our best value for the velocity dispersion of σ v = 6.2 +1.6 −1.3 km s −1 is significantly lower (∼3-σ) than what reported in the literature by both F09 and G19 (see also the discussion in the previous section), but closer now to the values observed for other similarly luminous dwarf galaxies of the Local Group (see e.g. Kirby et al 2014;Revaz & Jablonka 2018).…”
Section: Implications For Tucana's Dark Matter Halo Propertiessupporting
confidence: 76%
See 4 more Smart Citations
“…Our best value for the velocity dispersion of σ v = 6.2 +1.6 −1.3 km s −1 is significantly lower (∼3-σ) than what reported in the literature by both F09 and G19 (see also the discussion in the previous section), but closer now to the values observed for other similarly luminous dwarf galaxies of the Local Group (see e.g. Kirby et al 2014;Revaz & Jablonka 2018).…”
Section: Implications For Tucana's Dark Matter Halo Propertiessupporting
confidence: 76%
“…These results have also been reproduced by simulations (e.g. Schroyen et al 2013;Revaz & Jablonka 2018), which have shown that the shape of these gradients strongly depends on the combination of the stellar mass, SFH and dynamical history of the system under consideration, although their strength could be influenced by merger events (Benítez-Llambay et al 2016) or environmental effects such as tidal stripping (Sales et al 2010).…”
Section: Metallicity Propertiessupporting
confidence: 63%
See 3 more Smart Citations